BK002 Induces miR-192-5p-Mediated Apoptosis in Castration-Resistant Prostate Cancer Cells via Modulation of PI3K/CHOP - Park, Moon Nyeo; Park, Hyunmin; Rahman, Md. Ataur; Kim, Jeong Woo; Park, Se Sun; Cho, Yongmin; Choi, Jinwon; Son, So-Ri; Jang, Dae Sik; Shim, Bum-Sang; Kim, Sung-Hoon; Ko, Seong-Gyu; et al. (Frontiers in Oncology, 2022)
BK002 consists of Achyranthes japonica Nakai (AJN) and Melandrium firmum Rohrbach (MFR) that have been used as herbal medicines in China and Korea. AJN and MFR have been reported to anti-inflammatory, anti-oxidative, and anti-cancer activities, although the synergistic targeting multiple anti-cancer mechanism in castration-resistant prostate cancer (CRPC) has not been well reported. However, it is not well studied the drug resistance and transition to androgen-independent state of prostate cancer contribute to CRPC. Here, we re-ported that BK002 exerted cytotoxicity and apoptosis in CRPC PC3 cell lines and prostate cancer DU145 cell lines examined by cytotoxicity, western blot, LIVE/DEAD cell imaging assay, reactive oxygen species (ROS) detection, quantitative real-time polymerase chain reac-tion (RT-PCR), and transfection assays. The results from our investigation found that BK002 shown more cellular cytotoxicity than AJN and MFR alone, suggesting that BK002 exhibited potential cytotoxic properties. Consistently, BK002 increased DNA damage, activated p-γH2A.X and depletion of survivin activated ubiquitination of pro-PARP, caspase9 and caspase3. Notably, live cell imaging using confocal microscopy were analyzed that BK002 effectively increased DNA-binding red fluorescent intensity in PC3 and DU145 cells. Also, BK002 increased anti-proliferative effect with activating C/EBP homologous protein (CHOP) and significantly attenuation of PI3K/AKT expression. Notably, BK002 treated cell increased ROS generation and co-treatment of N-Acetyl-L-cysteine (NAC), an ROS inhibitor, signifi-cantly prevented ROS production and cellular cytotoxicity, representing ROS production is essential for initiating apoptosis in PC3 and DU145 cell. In addition, we found that BK002 significantly enhanced miR-192-5p expression and co-treatment with BK002 and miR-192-5p inhibitor significantly reduced miR-192-5p expression and cellular viability in PC3 and DU145 cells, indicating modulation of miR-192-5p-mediated apoptosis. Finally, we investi-gated that BK002-mediated CHOP upregulation and PI3K downregulation significantly re-duced and restrained by miR-192-5p inhibitor respectively, suggesting that anti-cancer effect of BK002 is associated with miR-192-5p/PI3K/CHOP pathway. Therefore, our study reveals that combination of AJN and MFR might be more effectively than single treatment against apoptotic activities of both CRPC cells and prostate cancer cells.